Employee Satisfaction With Working Space and Its Association With Well-Being—A Cross-Sectional Study in a Multi-Space Office - Lusa, Sirpa; Käpykangas, Sari Mirjami; Ansio, Heli; Houni, Pia; Uitti, Jukka (Frontiers in Public Health, 2019)
Introduction: Different kinds of shared and activity-based offices are common today and employees’ experiences, perceived health, well-being, satisfaction and productivity have been studied in different types and sizes of environments. Objectives: In this study we aimed to determine employee satisfaction with a multi-space office. We also aimed to find associations between satisfaction with working space and both individual and social well-being. Methods: A total of 91 employees from a multi-space office shared by six municipality-owned companies answered a self-administered questionnaire. Frequencies, percentages, averages and minimum and maximum values are used to describe the results. We used cross-tabulation and Pearson's Chi-Square test to study the associations and linear regression analysis to create a model describing the variability of workspace satisfaction. Results: The employees were most satisfied with the workspace furniture (82% of respondents) and most dissatisfied with workspace acoustics (44%). Workspace satisfaction was associated with self-satisfaction, good self-perceived future work ability and good recovery. As regards social factors, workspace satisfaction was associated with good atmosphere among colleagues and good social capital. Satisfaction with acoustics was also associated with good self-perceived future work ability, recovery and good social capital. Social capital best explained the general variation in workplace satisfaction. Conclusions: Many individual- and social-related well-being outcomes, and especially social capital, were associated with workspace satisfaction. To maintain workplace satisfaction and well-being, attention should be paid to the collaborative design, functionality and management of the used workspaces.